BUSINESS ACTIVITY DURING THE WAR: FEATURES, EFFICIENCY, STRATEGIES - MYHAILOVA, Olena; PYSARENKO, Svitlana; NOSENKO, Daryna; BONDARENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Entrepreneurship in times of war is a topic of increasing importance amidst geopolitical instability and armed conflicts. This article explores the nuances and challenges faced by entrepreneurs during wartime and analyses the effectiveness of strategies that can help them sustain and develop their businesses amid military operations.One of the key characteristics of entrepreneurial activity in war conditions is the high level of uncertainty and risk. War can lead to infrastructure destruction, disruptions in supply chains, and limitations on the movement of goods and services, significantly complicating business operations. However, entrepreneurs who possess adaptive skills and the ability to respond swiftly to changes can identify new opportunities in these challenges.Diversification is one of the pivotal strategies for entrepreneurs operating during wartime. Expanding the range of products and services, engaging alternative suppliers, and exploring new markets can reduce risks and enhance business resilience.The effectiveness of entrepreneurial activity during war depends on entrepreneurs’ ability to adapt to changes, make prompt decisions, and implement innovative approaches. This article underscores the importance of creating motivational programs for employees since their commitment plays a crucial role, and their productivity can substantially impact a company’s performance.Furthermore, the strategy of entrepreneurial activity during war should be oriented towards long-term success rather than mere survival. Entrepreneurs should view war as a temporary challenge and develop strategies focused on sustained growth after the war conclusion. Innovation plays a vital role in ensuring competitiveness during wartime, and entrepreneurs should invest in new technologies, products, and services that align with emerging market realities and needs.Collaboration with governmental bodies and military authorities is another crucial strategy for entrepreneurs, as it can provide stability and security for business operations during wartime. Interaction with such entities and cooperation on security issues can help entrepreneurs maintain the normal functioning of their enterprises.Entrepreneurship during war requires entrepreneurs to possess skills in adapting to change, formulating strategies, and being flexible in addressing challenges. Properly chosen actions and strategies can assist entrepreneurs in not only surviving but also thriving in their businesses during the war times.
Keywords: entrepreneurial activity; war; efficiency; strategy; relocation; sustainable development; business security